Epidemiological status of bovine tuberculosis in the State of Rio Grande do Sul, Brazil - Queiroz, Mariana Ramos (2016)
A study was conducted to determine the epidemiological status of bovine tuberculosis in the state of Rio Grande do Sul. The state was divided in seven regions, and in each of them, a pre-established number of farms was randomly sampled. In each farm, cows with age equal to or greater than 24 months were selected at random and submitted to the comparative cervical tuberculin test. The animals whose tests were inconclusive were retested with the same diagnostic procedure within a minimum interval of 60 days. In all, 9,895 animals from 1,067 farms were tested. An epidemiological questionnaire was applied in the farms in order to identify risk factors associated with bovine tuberculosis. The prevalence of infected herds in the state was 2.8% [1.8; 4.0] and that of infected animals was 0.7% [0.4; 1.0]. There was a trend towards a concentration of infected herds in the northern part of the state, with a predominance of dairy and mixed herds. The risk factors associated with the condition of infected herds were being a dairy herd (OR = 2.90 [1.40; 6.13]) and herds with 16 or more cows (OR = 2.61 [1.20; 5.49]). Thus, the best strategy to be adopted by the state is the implementation of surveillance systems to detect and remediate the infected herds, preferably incorporating elements of risk-based surveillance. In addition, the state must carry out a solid action of health education so that the producers test animals for bovine tuberculosis before introducing them in their herds